2019
DOI: 10.1038/s41467-019-12045-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-mediated nitric oxide depletion pre-adapts plants to hypoxia stress

Abstract: Timely perception of adverse environmental changes is critical for survival. Dynamic changes in gases are important cues for plants to sense environmental perturbations, such as submergence. In Arabidopsis thaliana , changes in oxygen and nitric oxide (NO) control the stability of ERFVII transcription factors. ERFVII proteolysis is regulated by the N-degron pathway and mediates adaptation to flooding-induced hypoxia. However, how plants detect and transduce early submergence signals rema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
214
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(220 citation statements)
references
References 44 publications
5
214
0
1
Order By: Relevance
“…Ethylene production during B. cinerea infection (Chaqu e et al, 2002) could have two consequences. On the one hand, it may contribute to induce the expression of ERF-VII at the transcriptional level (Hinz et al, 2010;Hartman et al, 2019), and on the other, it could enhance ERF-VII stability before hypoxia by increasing expression of the NO-scavenger PGB1 (Hartman et al, 2019). We observed production of ETH in the plants infected with B. cinerea (Fig.…”
Section: Researchmentioning
confidence: 73%
“…Ethylene production during B. cinerea infection (Chaqu e et al, 2002) could have two consequences. On the one hand, it may contribute to induce the expression of ERF-VII at the transcriptional level (Hinz et al, 2010;Hartman et al, 2019), and on the other, it could enhance ERF-VII stability before hypoxia by increasing expression of the NO-scavenger PGB1 (Hartman et al, 2019). We observed production of ETH in the plants infected with B. cinerea (Fig.…”
Section: Researchmentioning
confidence: 73%
“…In addition, passive ethylene entrapment acts as a rapid signal for submergence, and regulates many flood adaptive responses that include morphological and anatomical modifications to prevent hypoxia [8]. Ethylene also mediates metabolic hypoxia acclimation in the wetland species Rumex palustris and the model species Arabidopsis (Arabidopsis thaliana) [9][10][11]. In Arabidopsis, ethylene-mediated hypoxia tolerance is conserved in root and shoot meristems and is associated with enhanced expression of a conserved set of hypoxia-responsive genes when O 2 levels decline [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene also mediates metabolic hypoxia acclimation in the wetland species Rumex palustris and the model species Arabidopsis (Arabidopsis thaliana) [9][10][11]. In Arabidopsis, ethylene-mediated hypoxia tolerance is conserved in root and shoot meristems and is associated with enhanced expression of a conserved set of hypoxia-responsive genes when O 2 levels decline [10,12]. These hypoxia adaptive genes are predominantly controlled by the group VII Ethylene Response Factor (ERFVII) transcription factors RELATED TO APETALA2.2 (RAP2.2), RAP2.12 and RAP2.3 [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that when submergence is established, gas diffusion of ethylene is restricted, and it is trapped in the plant, triggering its signaling pathway at early submergence. When submergence is prolonged, ethylene synthesis is reduced due to hypoxia; group VII ethylene response factor (ERFVII) activity is activated by hypoxia signaling [30][31][32]. In our previous reports, we demonstrated that the NADPH oxidase RbohD plays a major role in the early stages of hypoxic stress responses.…”
Section: Discussionmentioning
confidence: 99%